Design and Development of ARM9 Evaluation Kit for Embedded Applications - Nikhil Alex Thomas; Sanket Dessai; S.G. ShivaPrasad Yadav; Shilpa Chaudhari (Institute of Advanced Engineering and Science, 2014)
In contrast with low end microprocessor, ARM9 core is quite a sophisticated processor. The Evaluation kit plays an important role in the prototype development and verification of the system design before taking to its actual system development hence it’s provide better confidence to the designer. In this paper a project for the Evaluation kit has been designed for embedded system engineer to implement and confirm the functionality of their operating systems which could lead to a comfortable deployment. The independent modules for the interfaces of the ARM9 processor have been designed and the schematics have been developed using OrCAD. From the tested schematics designed in OrCAD, the related PCB is designed using CADSTAR. An eight-layer board is designed for its signal integrity and complexity of the schematic designed. The designed PCB layer is then calibrated and Gerber files are then made and passed on the PCB board manufacturer for PCB fabrication. The PCB board made is then tested for interconnection continuity using multi-meter as the components are loaded on to the board.